Effect of a postpartum family planning intervention on postpartum intrauterine device counseling and choice: evidence from a cluster-randomized trial in Tanzania - Pearson, Erin; Bärnighausen, Till (BMC women's health, 2020)
The World Health Organization recommends postpartum family planning (PPFP) for healthy birth spacing. This study is an evaluation of an intervention that sought to improve women’s access to PPFP in Tanzania. The intervention included counseling on PPFP during antenatal and delivery care and introducing postpartum intrauterine device (PPIUD) insertion as an integrated part of delivery services for women electing PPIUD in the immediate postpartum period.
Gesehen am 18.09.2020